Planktonic foraminiferal flux seasonality in Subantarctic sediment traps: A test for paleoclimate reconstructions - King, AL; Howard, W (2003)
Sediment trap moorings deployed during 1997 and 1998 in the Subantarctic to Polar Frontal regions of the Southern Ocean reveal distinct seasonality in foraminiferal flux. Foraminiferal assemblages vary between each site, yet major species exhibit very similar patterns of seasonal succession which can be associated with changes in mixed layer depth. Enhanced foraminiferal productivity is also associated with periods of high biogenic silica and particulate organic carbon flux. On a broader scale, foraminiferal assemblages are strongly delineated by temperature. Temperature estimates derived from the assemblages using the modern analog technique (MAT) are mostly within 2.5 C of the satellite advanced very high resolution radiometer temperatures observed during the deployment period. This indicates that core top sediments included in the MAT database do reflect modern observed conditions at the sea surface, providing a robust technique for estimating past temperature change from foraminiferal assemblages in Southern Ocean environments.